2020
DOI: 10.1155/2020/6108619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moxibustion on Inflammatory Cytokines in Animals with Rheumatoid Arthritis: A Systematic Review and Meta‐Analysis

Abstract: Background. This study aims to systematically evaluate the effect of moxibustion on the level of inflammatory cytokines in animal models with rheumatoid arthritis (RA) and to provide evidence for the clinical application of moxibustion to the treatment of RA and related basic researches. Methods. The databases employed in this study include PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Periodical Database (VIP), SinoMed, and Wanfang Data Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Existing studies suggest that a large number of lymphocyte infltration can be seen in the lacrimal gland and conjunctiva of DED patients, and infammatory cells cause proinfammatory cytokine production [50], such as interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), and interleukin 6 (IL-6) [51] TCM theory holds that moxibustion has the functions of warming and dredging channels and collaterals, regulating qi and blood [52]. Also, studies suggest that moxibustion has an anti-infammatory and immune-regulation efect [53]. Te energy produced by the radiation process of moxibustion may provide activation for the pathological cells lacking energy and then regulate the body's immune Evidence-Based Complementary and Alternative Medicine function [54].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies suggest that a large number of lymphocyte infltration can be seen in the lacrimal gland and conjunctiva of DED patients, and infammatory cells cause proinfammatory cytokine production [50], such as interleukin 1β (IL-1β), tumor necrosis factor α (TNF-α), and interleukin 6 (IL-6) [51] TCM theory holds that moxibustion has the functions of warming and dredging channels and collaterals, regulating qi and blood [52]. Also, studies suggest that moxibustion has an anti-infammatory and immune-regulation efect [53]. Te energy produced by the radiation process of moxibustion may provide activation for the pathological cells lacking energy and then regulate the body's immune Evidence-Based Complementary and Alternative Medicine function [54].…”
Section: Discussionmentioning
confidence: 99%
“…In RA pathology, due to continuous antigen stimulation, the body reacts to inhibit the proliferating of T cells, which promotes the enhancement of negative costimulatory signals, and the expressions of mPD-1 and mPD-L1 are also increased correspondingly. Studies have found that moxibustion can upregulate the expression of anti-inflammatory cytokines (such as IL-4 and IL-10) and downregulate the level of proinflammatory cytokines (such as TNF-α and IL-1β) at the same time, thus restoring the balance of 1/ 2 [40,41]. As a key negative costimulatory molecule, PD-1 plays an important role in the activation of T cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…It can not only stimulate the self-regulation function of the human body but is also widely used in the prevention, treatment, and alleviation of diseases because of its simple, inexpensive test and easy operation. Modern studies have also proved that moxibustion can stimulate the internal regulation ability of the body by affecting the function of immune cells, the level of cytokines and signal pathways, and other multilinks and multitargets [18,27,28]. erefore, we choose the combination of moxibustion and drug therapy to explore a better treatment.…”
Section: E Efficacy Of Moxibustion Joint Swelling and Painmentioning
confidence: 99%
“…In China, moxibustion has a history of thousands of years in the treatment of RA, and its safety, effectiveness, and low price are its core competitiveness to be accepted by patients. Modern studies have found that the efficacy of moxibustion is related to inflammatory factors, signaling pathways, protein expression, and other aspects [18,19]. However, most of the relevant studies focus on animal studies, while few clinical studies.…”
Section: Introductionmentioning
confidence: 99%